Syndrome of normal pressure hydrocephalus: possible relation to hypertensive and arteriosclerotic vasculopathy. Issue 1 (January 1977) - Koto, A; Rosenberg, G; Zingesser, L H; Horoupian, D; Katzman, R
Abstract : A patient with clinical features of idiopathic normal pressure hydrocephalus, who responded dramatically to shunting, was found a necropsy to have a severe hypertensive and arteriosclerotic vasculopathy with multiple lacunar infarcts. There was no pathological evidence of thickened leptomeninges, fibrosis of the arachnoid villi, or Alzheimer's disease. An abnormal absorption mechanism was demonstrated with cisternography and by an increase in the concentration of homovanillic acid in the cerebrospinal fluid. It is suggested that vascular changes may play an important role in the pathophysiology in some cases of normal pressure hydrocephalus.